Financial Ratio Analysis as an Assessment Tool in Measuring the Company's Financial Performance at COCO 51.673.09 Lumajang Gas Station in 2017 -2019 - Dwi Putri Handayani; Noviansyah Rizal; Fetri Setyo Liyundira (International Journal of Accounting and Management Research, 2022)
The study aims to determine how the company's financial performance at SPBU COCO 51.673.09 Lumajang because the company's performance is a description of how the financial condition of a company regarding the good and bad state of a company which is a reflection of future work performance. To find out the financial performance required analysis of financial statements. The data analysis method used is quantitative descriptive method using measurement of liquidity, solvency, profitability and activity ratios. Based on the results of research from the liquidity ratio in 2017 to 2019, it can be said that it is not good because the company has difficulty in paying off current liabilities. Based on the solvency ratio in the period 2017 - 2019 is quite good where in each year it has increased, this is due to the low expenditure of companies sourced from loans. In the assessment of the activity ratio for the period 2017-2019, it can be said that it is quite good, judging from the development of the increase, this situation must be maintained. The profitability ratio in the period 2017 - 2019 is good which shows an increase in profit even though there is still a decrease.